Tracking SDG 7 : The Energy Progress Report 2019 - International Energy Agency; International Renewable Energy Agency; United Nations Statistics Division; World Bank; World Health Organization (World Bank, Washington, DC, 2019)
The Global Energy Progress Report 2019 provides a global dashboard on progress towards Sustainable Development Goal 7 (SDG7), which sets 2030 targets for reaching universal access to electricity and clean fuels and technologies for cooking, substantially increasing the share of renewable energy in the global mix, and doubling the rate of improvement of energy efficiency. All the data used in this pamphlet comes from the respective official source: for electrification, the World Bank; for clean fuels and technologies for cooking, the World Health Organization (WHO); for renewable energy, the International Energy Agency (IEA), the United Nations Statistics Division (UNSD) and the International Renewable Energy Agency (IRENA); and for energy efficiency, the IEA and UNSD. All projections are from the IEA’s World Energy Outlook. This report identifies best practices that have proven successful in recent years, as well as key approaches that policy makers may deploy in coming years. Recommendations applicable to all SDG 7 targets include recognizing the importance of political commitment and long-term energy planning, stepping up private financing, and supplying adequate incentives for the deployment of clean technology options. The following sections review progress in electricity access, access to clean cooking solutions, renewable energy, and energy efficiency. The Energy Progress Report reviews progress to 2017 for energy access and to 2016 for renewable energy and energy efficiency, against a baseline year of 2010. Its methodology is detailed at the end of each chapter.